THE ROLE OF RESOURCE CONSUMPTION ACCOUNTING IN COST MANAGEMENT AN APPLIED STUDY IN AL-NARGIS PIPE MANUFACTURING COMPANY - Dr. Jaber Hussein Ali; Batool Abdul Ali Dhiqam Al-Mansouri (Scholars Digest Publishing, 2025)
As a result of the rapid development in the modern manufacturing environment, economic units face several challenges, including resource scarcity and intense competition. These challenges make it difficult for traditional cost systems to accurately reflect the impact of resource usage and hinder management’s ability to access precise information needed for sound decision-making.
Keywords: Resource Consumption Accounting, Cost Management.